2020
DOI: 10.1111/1365-2435.13723
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in intraspecific variation in root traits are species‐specific along an elevation gradient

Abstract: Patterns in intraspecific variation in root traits are species-specific along an elevation gradient Abstract 1. Intraspecific trait variation is an important driver of plant performance in different environments. Although roots acquire essential resources that vary with the environment, most studies have focused on intraspecific variation in leaf traits, and research on roots is often restricted to a few species. It remains largely unclear how and to what extent root traits vary with the environment and whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 80 publications
8
83
5
Order By: Relevance
“…Here, we observed very similar trade‐offs between global species means and individual‐based datasets. Although we deem our results to be generally robust, there remains substantial uncertainty surrounding the amount and importance of intraspecific variation and plasticity in trait analyses (Sultan, 2000; Weemstra et al ., 2021). Additional work is needed to investigate the ranges of variation within and across species and, given the focus of the current study, it would be particularly interesting to know whether there is more variation in above‐ or belowground traits.…”
Section: Conclusion and Ecological Considerationsmentioning
confidence: 99%
“…Here, we observed very similar trade‐offs between global species means and individual‐based datasets. Although we deem our results to be generally robust, there remains substantial uncertainty surrounding the amount and importance of intraspecific variation and plasticity in trait analyses (Sultan, 2000; Weemstra et al ., 2021). Additional work is needed to investigate the ranges of variation within and across species and, given the focus of the current study, it would be particularly interesting to know whether there is more variation in above‐ or belowground traits.…”
Section: Conclusion and Ecological Considerationsmentioning
confidence: 99%
“…Here, seedlings from different populations of Norway spruce grew in controlled chamber environments that mimicked natural light and temperature cycles within a latitudinal gradient, revealing trait‐dependent patterns of among‐population variation that could signal adaptation to varied environmental factors. Based on the current results and related common‐garden and in situ studies on conifers (Ostonen et al 2011, 2017, Zadworny et al 2016, Weemstra et al 2021), traits that express root system size, the proportion of fine roots within root systems and biomass allocation to roots versus shoots may be more useful belowground complements to climate‐related shoot traits than branching intensity and specific root length. Together, the coexisting intraspecific phenomena of genetic diversity, multidimensionality of functional traits and phenotypic plasticity may echo robust survival strategies of long‐lived species in habitats that are characterised by consequential spatial and temporal heterogeneity and changing selective pressures (Aitken et al 2008, Laughlin 2014).…”
Section: Discussionmentioning
confidence: 65%
“…The finding of no latitudinal trend in branching intensity and specific root length within this geographic region is in agreement with the results of Ostonen et al (2017) who measured the same traits in fine roots of the same species at five sites between 60° and 68°N in Finland. More recently, Weemstra et al (2021) noted that variation in branching intensity and specific root length of fine roots in Norway spruce in situ was higher within elevations than across a 600‐m elevational range in the French Alps. However, Ostonen et al (2011) found that root tip length and fine root biomass were larger in higher‐latitude Norway spruce stands in Finland, and a common‐garden study with eastern European origins of Scots pine described a parallel positive correlation between latitude and the percentage of absorptive fine roots (Zadworny et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We present data collected in 2018, at six altitudes along an elevational gradient (1400–2400 m), at Massif de Belledonne, France (Table 1 , file 1, [ 5 ]). Bedrock was composed of Variscan metamorphic rocks and ophiolitic complexes.…”
Section: Data Descriptionmentioning
confidence: 99%